Answers

The Brainliest Answer!
2016-04-08T10:50:33+05:30
The equations are: (Solving by Elimination Method)

  5x   - 6y = 8 ------------- (1)* 3     
-15x + 7y = 9--------------(2) * 1

∴ 15x - 18y = 24                (Adding)
  -15x + 7 y = 9
________________
∴  -11y = 33
y = -3

Putting y= -3 in (1)

∴ 5x - 6(-3) = 8
∴ 5x + 18 = 8
∴ 5x = 8 - 18
∴ 5x = -10
∴ x = -2

Thus, solution of pair of linear equations in two variables is (x,y) = (-2,-3).
 
1 5 1
Please mark as brainliest
can you solve mine other questions too please
Yes sure
2016-04-08T11:05:32+05:30
5x - 6y = 8 ------------- eq (1) -15x + 7y = 9--------------eq (2) By adding the eq (1 ) and (2) ∴ 15x - 18y = 24 -15x + 7 y = 9 ________________ ∴ -11y = 33 ∴ y = -3 Putting y= -3 in (1) ∴ 5x - 6(-3) = 8 ∴ 5x + 18 = 8 ∴ 5x = 8 - 18 ∴ 5x = -10 ∴ x = -2 So x =-2 and Y =-3 PLZ MARK AS A BRAINLIEST.
1 5 1